Synthetic biology for combating leishmaniasis - Khandibharad, Shweta; Singh, Shailza (Frontiers in Microbiology, 2024)
Leishmaniasis is a neglected tropical disease caused by protozoan parasites of the Leishmania genus. Despite the efforts to control and treat the disease, it still remains a major public health problem in many countries. Synthetic biology is a rapidly evolving interdisciplinary field that combines biology, engineering, and computer science to design and construct novel biological systems. In recent years, synthetic biology approaches have shown great promise for developing new and effective strategies to combat leishmaniasis. In this perspective, we summarize the recent advances in the use of synthetic biology for the development of vaccines, diagnostic tools, and novel therapeutics for leishmaniasis.